"Pulmonary Endothelial Cell Barrier Enhancement by Novel FTY720 Analogs: Methoxy-FTY720, Fluoro-FTY720, and β-Glucuronide-FTY720". (January 2016) - Camp, Sara M.; Chiang, Eddie T.; Sun, Chaode; Usatyuk, Peter V.; Bittman, Robert; Natarajan, Viswanathan; Garcia, Joe G.N.; Dudek, Steven M.
Highlights: Novel therapeutics are needed to treat vascular leak in ARDS. This study characterizes effects of 4 novel FTY720 analogs on vascular permeability. These analogs employ S1P-related signaling pathways to alter permeability. Three novel analogs are barrier-enhancing comparable or superior to FTY720/S1P. These mechanistic insights may assist in novel ARDS therapeutic development. Abstract: Effective therapeutic agents are lacking for the prevention and reversal of vascular leak, a frequent pathophysiologic result of inflammatory processes such as acute respiratory distress syndrome (ARDS) and sepsis. We previously demonstrated the potent barrier-enhancing effects of related compounds sphingosine 1-phosphate (S1P), the pharmaceutical agent FTY720, and its analog (S)-FTY720 phosphonate (Tys) in models of inflammatory lung injury. In this study, we characterize additional novel FTY720 analogs for their potential to reduce vascular leak as well as utilize them as tools to better understand the mechanisms by which this class of agents modulates permeability. Transendothelial resistance (TER) and labeled dextran studies demonstrate that (R)-methoxy-FTY720 ((R)-OMe-FTY), (R)/(S)-fluoro-FTY720 (FTY-F), and β-glucuronide-FTY720 (FTY-G) compounds display in vitro barrier-enhancing properties comparable or superior to FTY720 and S1P. In contrast, the (S)-methoxy-FTY720 ((S)-OMe-FTY) analog disrupts lung endothelial cell (EC) barrier integrity in TER studies in association with actin stress fiber formation and robust intracellular calcium release, but independent of myosin light chain or ERK phosphorylation. Additional mechanistic studies with (R)-OMe-FTY, FTY-F, and FTY-G suggest that lung EC barrier enhancement is mediated through lipid raft signaling, Gi-linked receptor coupling to downstream tyrosine phosphorylation events, and S1PR1-dependent receptor ligation. These results provide important mechanistic insights into modulation of pulmonary vascular barrier function by FTY720-related compounds and highlight common signaling events that may assist the development of novel therapeutic tools in the prevention or reversal of the pulmonary vascular leak that characterizes ARDS.